Strategi Guru dalam Menangani Anak Speech Delay di RA Gerhana Alauddin - Syamsuardi; Sari, Nur Raoda; Dzulfadhilah, Fitriani; Lismayani, Angri (Early Childhood Islamic Education, 2024)
Early childhood education is provided as guidance and stimulation, so that children grow and develop according to their stages. One of the most important things in child development is language development. Speech delay is a condition where a child does not develop the ability to speak according to his age, which generally occurs in children. The aim of this research is to find out and describe the strategies implemented by teachers in dealing with speech delayed children at RA Gerhana Alauddin. This research uses a qualitative approach and a case study type of research. Data collection techniques in this research are observation, interviews and documentation. The data sources for this research are school principals, teachers and students who experience speech delays. Checking the validity of the data was carried out by triangulating techniques and sources. The data analysis techniques for this research are data reduction, data presentation, and drawing conclusions. The results of the research at RA Gerhana Alauddin, teachers implemented several strategies in dealing with speech delayed children, namely (1) correcting pronunciation errors, (2) encouraging children to tell stories, (3) providing visual aids such as coloring books, and (4) reading fairy tales. With this strategy children show improvement in spelling words, express their desires verbally, and respond without using non-verbal language.